Glance into solid-state transformer technology: a mirror for possible research areas - Bashir Musa Umar; Yusuf Jibril; Boyi Jimoh; Abdullahi Bala Kunya; Yusuf Abubakar Maiwada; Safiya Aliyu; Musa Mohammed (Journal of Applied Materials and Technology, 2020)
Solid-State Transformer (SST), a power electronics based transformer is an emerging technology in electric power system. The transformer is being investigated to completely replace existing Line/Low Frequency Transformer (LFT). SST is composed of either of the two topologies: AC-DC-AC, two steps approach; or AC-AC, single-step approach. The two steps approach consists of three stages: AC-DC; DC-DC; and DC-AC stages. The DC-DC stage is made up of a boost DC-DC converter, a DC-AC inverter and a High Frequency Transformer, HFT. Therefore, SST performs the tasks of LFT by means of power electronic converters and HFT. The main essence of SST is to provide solution to the problem of bulkiness and heaviness of the LFT in the power distribution network. This is with the view to providing reduction in construction cost, cost of maintenance and transportation. The power electronics transformer provides numerous advantages which are grouped into: The transformer has high power density; it functions in blackouts and brownouts; and it provides easy means of distributed renewable energy integration into associated grid. Therefore, this paper provides a glance into the technology of the SST for its better understating and promotion of research activities in the area.